Pressurized Nozzle‐Based Solvent/Anti‐Solvent Process for Making Ultrafine ϵ‐CL‐20 Explosive. Issue 7 (18th April 2017) - Gupta, Shallu; Kumar, Pal Dinesh; Sharma, Sandeep; Kaur, Gurvinder; Agarwal, Arun; Lata, Prem
Abstract: CL‐20 explosive is one of the most recent and powerful explosives. It has very high potential in futuristic applications but at present it has limitations of sensitivity to mechanical stimuli. Among the four different polymorphs (α, β, γ, and ϵ), ϵ‐polymorph has better stability and shock/detonics properties. However, preparation of pure ϵ‐polymorph is a challenging task particularly in terms of repeatability and polymorphism. In our research work, pressurized nozzle based solvent/anti‐solvent process (PNSAP) was developed for the preparation of ultrafine ϵ‐CL‐20 explosives with high repeatability, purity, and yield. To get ultrafine particle size, shape, distribution and yield, various process parameters/ variables such as solvent type, anti‐solvent type, dosing rate, stirring rate, ultra‐sonication, and temperature were identified and prioritized using the weighted average method of Analytical Network Process (ANP) techniques. It was observed that ultrafine ϵ‐CL‐20 particle size in the range of 2 to 3 μm can be obtained using this process. The ϵ‐polymorph was confirmed by FT‐IR characterization. The main feature of this PNSAP process is that it is a laboratory scale table‐top pilot plant which is simple, cost‐effective, safe and repeatable for continuous batch production of ultrafine ϵ‐CL‐20 at the rate of 100 grams per hour. Abstract :